The socialist good life : desire, development, and standards of living in Eastern Europe - Scarboro, Cristofer, 1972-; Mincyte, Diana; Gille, Zsuzsa (Bloomington : Indiana University Press, 2020)
"What does the good life mean in a "backward" place? As communist regimes denigrated widespread unemployment and consumer excess in Western countries, socialist Eastern European states simultaneously legitimized their power through their apparent ability to satisfy consumers' needs. Moving beyond binaries of production and consumption, the essays collected here examine the lessons consumption studies can offer about ethnic and national identity and the role of economic expertise in shaping consumer behavior. From Polish VCRs to Ukrainian fashion boutiques, tropical fruits in the GDR to cinemas in Belgrade, The Socialist Good Life explores what consumption means in a worker state where communist ideology emphasizes collective needs over individual pleasures"--
Includes bibliographical references and index.
Keywords: Socialism -- Europe, Eastern -- History; Communism -- Europe, Eastern -- History; Consumption (Economics) -- Europe, Eastern; Lifestyles -- Europe, Eastern; Europe, Eastern -- Politics and government -- 1945-1989.